2019
DOI: 10.1017/s095026881900150x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, molecular characterisation and antimicrobial susceptibility ofNeisseria gonorrhoeaeisolates in Madrid, Spain, in 2016

Abstract: With the aim to elucidate gonococcal antimicrobial resistance (AMR)–risk factors, we undertook a retrospective analysis of the molecular epidemiology and AMR of 104 Neisseria gonorrhoeae isolates from clinical samples (urethra, rectum, pharynx and cervix) of 94 individuals attending a sexually transmitted infection clinic in Madrid (Spain) from July to October 2016, and explored potential links with socio-demographic, behavioural and clinical factors of patients. Antimicrobial susceptibility was determined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
(46 reference statements)
1
2
0
Order By: Relevance
“…In this region of the north of Spain, the percentage of resistance was of the same order as recent data obtained from Madrid [20] and Barcelona [21,22], and also of those reported in other European countries [23]. As expected, the highest percentage of resistance was detected for ciprofloxacin (>45%).…”
Section: Discussionsupporting
confidence: 88%
“…In this region of the north of Spain, the percentage of resistance was of the same order as recent data obtained from Madrid [20] and Barcelona [21,22], and also of those reported in other European countries [23]. As expected, the highest percentage of resistance was detected for ciprofloxacin (>45%).…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies on the molecular epidemiology of NG published in Spain are based on NGMAST, with G1407, G2992 and G2400 being the most prevalent genotypes in Southern Spain, 25 Northern Spain 24 and Madrid, 36 respectively. The only study in which WGS was used was that by Francés‐Cuesta et al 37 (data not published), which included 342 isolates from several areas of the national territory.…”
Section: Discussionmentioning
confidence: 99%
“…In Spain, azithromycin sensitivity studies of NG have been reported by the gradient diffusion methods. The prevalence of azithromycin resistance contrasts between 2-12% [10][11][12][13]. However, no studies using NAAT methods have been described.…”
Section: Discussionmentioning
confidence: 99%